Macroeconomic fluctuations in Europe: demand or supply, permanent or temporary? - Peter R. Hartley; Jr. Joseph A. Whitt (Federal Reserve Bank of Atlanta, 1997)
We use generalized method of moments to estimate a rational expectations aggregate demand-aggregate supply macroeconomic model for five European economies. Our aim is to examine whether supply or demand shocks have predominated in the major European economies during the post-war era and whether shocks of either type have been primarily temporary or permanent in nature. The estimation procedure is an alternative to estimating and interpreting vector autoregressions under restrictions either of the Bernanke-Sims variety or the Blanchard-Quah variety or to performing calibration exercises. ; We find that all four types of shocks (permanent supply, permanent demand, temporary supply, and temporary demand) are needed to account for the data on output and inflation. Permanent or temporary demand shocks have been the dominant source of variance in output growth in four of the five countries, but there is no consistent pattern for inflation.
Keywords: 330; Business cycles; Econometric models; Europe; Macroeconomics